The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/jpm11080761
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Mass Spectrometry Discovered Human IgG Sialylation as a Potential Biosignature for Kidney Function

Abstract: Immunoglobulin G (IgG) N-glycosylation was discovered to have an association with inflammation status, which has the potential to be a novel biomarker for kidney diseases. In this study, we applied an ultra-high performance liquid chromatography–tandem mass spectrometry (UHPLC-MS/MS) method to plasma and urine samples from 57 individuals with different levels of kidney function. Natural abundances of total IgG, IgG1, IgG2, and IgG3 subclasses in plasma showed positive correlations to the estimated glomerular f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…Studies have identified decreased levels of sialylated glycans in renal disease patients ( 47 ). In another study, a decrease in GP16 and GP18 levels was found in CKD patients ( 48 ), aligning with our research findings. Galactosylation, a precursor of sialylation, frequently shows a similar directional alteration ( 32 ).…”
Section: Discussionsupporting
confidence: 92%
“…Studies have identified decreased levels of sialylated glycans in renal disease patients ( 47 ). In another study, a decrease in GP16 and GP18 levels was found in CKD patients ( 48 ), aligning with our research findings. Galactosylation, a precursor of sialylation, frequently shows a similar directional alteration ( 32 ).…”
Section: Discussionsupporting
confidence: 92%
“…Barrios and Menni et al demonstrated that 14 different IgG glycan traits belonging to galactosylation, sialylation, and bisecting features were associated with kidney function [21]. Kao et al showed that IgG1 sialylation was associated with eGFR (Estimated Glomerular Filtration Rate) values, confirming that the decrease of sialylated IgG is an indicator of the inflammatory status of individuals with lower kidney function [43].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the changes in glycosylation patterns with a notable increase in fucose exposure correlate with the late stage of sepsis when neutrophil elastase activity is elevated. This made neutrophil-associated enzymatic release a potential target in studies of the etiopathogenesis of sepsis [ 65 , 67 ]. However, the relationship between this correlation has not been fully revealed.…”
Section: Discussionmentioning
confidence: 99%